Pengaruh Dukungan Sosial, Self-Esteem Dan Self-Efficacy Terhadap Orientasi Masa Depan Pada Remaja Akhir - Preska, Lebis; Wahyuni, Zulfa Indira (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
This study was conducted to determine the influence of social support, self-esteem and selfefficacy to future orientation in adolescence. The subject in this research were 200adolescence were taken by non probability sampling and purvosive technique. CFA(Confirmatory Factor Analysis) was used to test the validity of instrument and MultipleRegression Analysis was used to test the research hypothesis. The result showed that there isan effect of social support, self-esteem and self efficacy to future orientation in adolescence.Minor hypothesis test result indicated that emotional support, self esteem and self-efficacyhave a significant effect on future orientation. The result also showed the proportion of thevariance of future orientation described by all independent variables was 29.7%, while70.3% was influenced by other variables outside of this research.Â DOI:Â 10.15408/tazkiya.v22i1.8160